Disability, Inclusion and Language-in-Education Policy in the Global South: The Colombian Context - Rosa Dene David; Kimberley Brown (Center for Educational Policy Studies Journal)
This paper calls for a shift related to English language-in-education policy and inclusive education initiatives in Colombia to ensure that English language learners with disabilities receive equitable and inclusive classroom instruction that is context-appropriate. We call for English language initiatives and policies to draw from theories and practices from both the Global South and the Global North in order to teach towards inclusive education. Trends in both English language teaching and inclusive education have drawn upon the Global North for solutions, which cannot be systemised to fit one international standard. Instead, using the Colombian context as an example, the present paper suggests a localised approach to meeting the educational needs of English language learners that incorporates inclusive education at the institutional level. This model would favour the work of scholars within the region to ensure that all students receive equitable classroom instruction that builds in Global South epistemologies and localised ways of knowing.